PENGARUH MODEL PEMBELAJARAN KOOPERATIF DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VIII SMP KATOLIK SANTA MARIA MEDAN - Erikson Simbolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2015)
The purpose of this study are: (1) to assess the learning outcomes of Bahasa Indonesia of the students who are taught using Jigsaw model of cooperative learning and the learning outcomes of Bahasa Indonesia of the students who are taught using STAD cooperative learning model. The population of this study are all the eighth grade students of St. Maria Chatolic Junior High School, Medan, which consists of three classes: Class VIII A, Class VIII B, Class VIII C. The samples choosen to use the Jigsaw cooperative learning model are determined randomly from the students of Class VIII A (31 students).The samples who will use the STAD cooperative learning model randomly coosen from the students of Class VIII C (32 students). The research instrument used to measure the learning outcomes is the multiple choice test, whereas questionaire is used to obtain the data of the motivation of the students, normality test using Liliefors test, homogenity test using Fisher and Barlett test. Data analysis technique is Anova at significance level α = 0.05, followed by Scheffe test. Kata Kunci : Model pembelajaran tipe STAD, Jigsaw, motivasi belajar